2018
DOI: 10.1039/c8ew00188j
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable amine-functionalized magnetic nanoparticles for efficient demulsification of crude oil-in-water emulsions

Abstract: Produced water from the oil and gas industry often contains stable crude oil-in-water emulsions that are typically difficult to treat with conventional separation methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…The comparison of the E S between Fe 3 O 4 @HA@PDDA and other magnetic demulsiers in the literatures is summarized in Table 1. It was found that most of the demulsiers [12][13][14][15][16][17]40,41 with amino group show excellent demulsication performance up to 90%, while Fe 3 O 4 @HA@PDDA NPs have higher oil-water separation efficiency with the least dosage except for quaternized chitosan (QC)-graed MNPs. 16,17 In addition, Fe 3 O 4 @HA@PDDA NPs show higher oil-water separation efficiency for ultra-small particle emulsions (the average size of oil droplet is 247 AE 35 nm).…”
Section: Oil-water Separation Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The comparison of the E S between Fe 3 O 4 @HA@PDDA and other magnetic demulsiers in the literatures is summarized in Table 1. It was found that most of the demulsiers [12][13][14][15][16][17]40,41 with amino group show excellent demulsication performance up to 90%, while Fe 3 O 4 @HA@PDDA NPs have higher oil-water separation efficiency with the least dosage except for quaternized chitosan (QC)-graed MNPs. 16,17 In addition, Fe 3 O 4 @HA@PDDA NPs show higher oil-water separation efficiency for ultra-small particle emulsions (the average size of oil droplet is 247 AE 35 nm).…”
Section: Oil-water Separation Performancementioning
confidence: 99%
“…The resulting amphiphilic demulsier exhibited excellent oilwater separation performance in emulsions with oil droplet sizes ranging 0.4 to 10 mm. [12][13][14] Lü et al produced Fe 3 O 4 MNPs using a solvothermal method, followed by aminopropyl functionalization using a modied Stöber method. The surface of the material was further modied with aldehyde and graed with chitosan (CS).…”
Section: Introductionmentioning
confidence: 99%
“…coated with a surface-active agent, they act as the carrier for the chemical that has the added benefit of being able to be manipulated by an external magnet. This magnetism has been utilized to separate the water from the demulsifying compound during water treatments (Wang et al, 2018). The use of bare or uncoated iron oxide nanoparticle to the oil and gas industry has been limited.…”
Section: Functionalized Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…Determining the lowest concentration of nanoparticles allowable to maintain oil removal efficiencies provides substantial evidence and purpose to the practical use of these nanoparticles on a larger scale. Primary nanoparticle concentrations were selected from the literature (Wang, 2018) and were later reduced by one-half for the tests later used to determine critical nanoparticle concentrations for the treatment process. Table 3.4 summarizes each nanoparticle sample the corresponding concentrations (mg/mL) tests that were conducted.…”
Section: Table 32 Test Matrix For Emulsion Preparation and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation